Estimating the Lagged Response of Profitability on Labour Ratio - Gaspar, Attila (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
This paper investigates recent trends of production factor – including both capital and labour – ratios in the EU-27 based on national accounts data. These output elasticities are typically expected to be constant, however, both theoretically and empirically, these assumptions are frequently violated for a variety of reasons.In this paper a lagged response is introduced and investigated: changes of profitability can affect labour force adjustments with a delay. Granger causality tests confirm lagged behaviour. Structural VAR estimations show the strongest impact over the span of two to five quarters and the effect is moderate.